Noise disturbance investigation and quality improvement in precision component machining. - Juluri Bala Krishna (2014)
The purpose of this project is to 1) investigate the sources of dimensional variation and 2) recommend several control measures for countering them during the machining of a precision component. The investigation involved shop-floor observations supported with analyses on dimensional data collected during the project. In order to achieve the second objective, the project involved implementing three methodologies. Firstly, Finite Element Analysis (FEA) was used to study the structural deformation of the component under the influence of machining forces. Subsequently, design of experiments (DOE) was carried out to determine the significant process inputs as well as their nominal levels for a robust process operation. These experiments resulted in a recommended set of optimal process parameters, which were applied on a test machine, and its process performance is reported. Finally, a specific feedback control system-Cycle to Cycle (CTC) control was suggested and evaluated to reduce the noise disturbance. The final outcome of this project was the achievement of overall quality improvement by these methodologies in a systematic approach.